The role of oxidative stress in spinal cord ischemia reperfusion injury: mechanisms and therapeutic implications - Xing, Yu; Xiao, Yuan-zhang; Zhao, Min; Zhou, Jiang-jun; Zhao, Kai; Xiao, Chun-lin (Frontiers in Cellular Neuroscience, 2025)
Spinal cord ischemia/reperfusion injury (SCIRI) is a serious disease that leads to the loss of sensory and motor functions and is a common complication after spinal cord injury, spinal cord degeneration or thoracic and abdominal aortic surgery. At present, the spinal cord is mainly protected from ischemic injury through treatment strategies such as hypothermia, surgery and drug assistance, but these intervention measures cannot effectively improve these conditions. SCIRI is a complex process that leads to cell damage and death. Among them, oxidative stress is an important pathological event of ischemia/reperfusion injury. Oxidative stress can initiate multiple inflammatory and apoptotic pathways, triggering a series of destructive events such as inflammatory responses and cell death, further deteriorating the microenvironment at the injured site, and leading to neurological dysfunction. Based on the important role of oxidative stress in SCIRI, we believe that targeted inhibition of oxidative stress responses can effectively reduce secondary injuries caused by trauma, which has a certain positive effect on the rehabilitation and prognosis of patients with SCIRI. This review systematically expounds the spatiotemporal dynamic characteristics of oxidative stress during the SCIRI process and its molecular regulatory network, with a focus on analyzing the multivariate generation mechanism of ROS. To deeply explore the regulatory effects of ROS on pathological processes such as neuronal death, inflammatory response and blood-spinal barrier disruption under SCIRI conditions, as well as its interaction patterns with signaling pathways. In order to form a systematic treatment for SCIRI caused by oxidative stress and promote the recovery of neurological function after injury. This review is helpful for us to understand the effect of oxidative stress on SCIRI and provides a theoretical basis for the treatment of SCIRI based on oxidative stress.